Levodopa-induced Dyskinesias in Parkinson's Disease: Current Knowledge and Future Scenarios - Francesca Morgante (Frontiers Research Topics, 2015)
This topic aims to pool the most recent advances in the phenomenology and pathophysiology of levodopa-induced dyskinesias. The papers in this eBook have strongly contributed to reduce the gaps in our knowledge of LIDs pathogenesis.